ECONOMIC ANALYSIS OF DRY SEASON VEGETABLE FARMING AMONG WOMEN IN MAKURDI LOCAL GOVERNMENT AREA OF BENUE STATE, NIGERIA (FULafia Journal of Science and Technology, 2023)
The study assessed dry season vegetable farming among women in Makurdi Local Government Area of Benue State. A total sample size of 60 dry season vegetable farmers was used for the study. Information for the study was collected using a well-structured questionnaire administered within four weeks to the respondents. Simple descriptive statistics (such as frequency counts, means and percentages), multiple regression and gross margin analysis were used to analyze the data. The results revealed that majority (70.0 %) of the women engaged in dry season vegetable farming were within the age bracket of 31-40 and 71.1% were literate
Keywords: Vegetable; Dry Season; Micronutrient and Irrigation Farming